AB1195 CO-RELATION BETWEEN SELF EFFICACY, DEPRESSION AND PAIN AMONG CAREGIVERS WITH AND WITHOUT ARTHRITIS. (2nd June 2020) - Sheth, K.; Simard, J.; Ritter, P.; Lorig, K.
Abstract : Background: People with arthritis, like others, are often informal caregivers. Caregiving adds burdens of stress and depression. Caregiver studies have shown these to be mitigated by self-efficacy or the confidence to achieve specific caregiving behaviors. Caregivers with arthritis have seldom been studied. We have been unable to find studies specific to caregiving and self-efficacy as they apply to those with and without arthritis. In this study, we evaluated the relationship between self-efficacy, pain, and depression among caregivers with and without arthritis. Objectives: 1)To examine the correlation between caregiver self-efficacy and depression and pain. 2). To examine how these correlation differ for caregivers with and without arthritis. Methods: A caregiver questionnaire was distributed via social media, mainly list serves and blogs to a convenience sample. Those receiving the links were urged to send them to other populations. Respondents self-reported arthritis and weekly hours spent caregiving. They reported pain using a pain (visual numeric scale (1-10)), depression with the Patient Health Questionnaire (PHQ-8), and Self-Efficacy was reported with the short caregiver self-efficacy scale). For caregivers and non-caregivers we compared caregiving hours, pain, depression and self-efficacy. We examined the distribution of caregiving hours by arthritis status and plotted mean pain scores by caregiving hours for caregivers with and without arthritis. The correlation between depression and self-efficacy was measured using Pearson correlation coefficient overall and by arthritis status. Results: Over two weeks 155 individuals responded, with data on self-reported arthritis status. Of the respondents, 88% were female and 64% were 50-69 years of age. 46% self-reported arthritis (osteoarthritis was the most common type). Nearly 25% of caregivers reported spending less than 10 hours weekly on caregiving, while approximately 23% reported at the other end of the extreme (at least 40 hours weekly). The distribution by arthritis status of the caregiver is provided in Table 1 . Caregivers with arthritis reported higher pain in the past week. Mean pain score among caregivers with arthritis was 4.4 (SD 2.2) compared to 2.7 (SD 1.7) among caregivers without arthritis (figure 1 ). This divergence widened for caregivers with 40 or more hours of caregiving. There was a strong negative correlation (Pearson correlation= – 0.473, p-value <0.0001) between depression and self-efficacy. The correlation was -0.59 for caregivers without arthritis (p=<0.0001, n=74 with data on all three variables) compared to the caregivers self-reporting arthritis (r=-0.35, p=0.006, n=60 with data on all three variables). Conclusion: This study suggests that lower caregiver self-efficacy has a direct and strong association with higher depressive symptoms and that this is more pronounced among caregivers with arthritis. This study also shows that caregivers with arthritis have more pain than caregivers without arthritis, and that this peaks and remains consistent for those doing twenty or more hours of caregiving weekly.. The stronger negative correlation of depression and self-efficacy among patients without arthritis may be explained by other independent contributors (such as pain) to depression in caregivers with arthritis. References: [1]Lorig K, Ritter PL, Laurent DD, Yank V. Building Better Caregivers: A Pragmatic 12-Month Trial of a Community-Based Workshop for Caregivers of Cognitively Impaired Adults. J Appl Gerontol . 2019;38(9):1228–1252. doi:10.1177/0733464817741682 Disclosure of Interests: None declared